Youth Farmer Empowerment and Sustainable Livelihoods in Gayo Coffee Production: Institutional Strategies of KBQ Baburrayyan Coffee Cooperative in Bener Meriah - Karina Cibro; Deya Amanda (Universitas Teuku Umar, 2026)
This study aims to examine the role of the BQ Baburrayyan Coffee Cooperative in empowering coffee farmers in Bener Meriah Regency, Aceh, particularly in promoting sustainable coffee farmer regeneration. Bener Meriah is Indonesia's largest arabica coffee production center, with a cultivated area of 34,524.41 hectares and an annual production of 26,420 tons. However, the sector faces a serious threat in the form of the aging farmers phenomenon, where the average age of coffee farmers reaches 55 years and only 15 percent of farmers are under 40 years old. This research employs a qualitative method with a case study approach, conducted through in-depth interviews, field observations, and literature review. Analysis was carried out using Muhtarom's (2016) role theory, which encompasses three institutional functions: facilitator, motivator, and dynamizer. The findings reveal that BQ Baburrayyan Cooperative has implemented all three roles through various empowerment programs, including: (1) as a facilitator, providing broader market access, laboratory quality testing, and reducing farmers' dependence on middlemen; (2) as a motivator, offering guidance and technical assistance to both senior farmers and young generations; and (3) as a dynamizer, conducting field mentoring, modern agricultural technology training, and production quality development. Nevertheless, these three roles have not yet functioned optimally due to persistent obstacles: low parental participation in encouraging children to pursue coffee farming, social stigma attached to the farming profession, and diminishing interest among young people given the wider array of career alternatives.